Chile : Selected Issues. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper examines the effect of lower copper prices on Chile's growth at various time horizons. This paper discusses the copper outlook and suggests that the fall in copper prices is likely to have a persistent (although not permanent) effect on GDP growth. It argues that copper prices are unlikely to return to historical highs in the near future. The paper also provides theoretical and empirical evidence supporting the view that long-term GDP growth will not be affected, but the transition toward a lower GDP level can take up to a decade.